An Energy Culture Maturity Conceptual Framework on Adopting Energy-Efficient Technology Innovations in Buildings - Dumindu Soorige; Gayani Karunasena; Udayangani Kulatunga; Muhammad Nateque Mahmood; Lalith De Silva (Journal of Open Innovation: Technology, Market and Complexity, 2022)
ABSTRACT: The building sector is identified as the leading global energy consumer. Adopting energy-efficient technology innovations has been recognised as the most promising approach to reducing energy consumption in buildings. However, such technology adoption is considerably lacking due to traditional techno-economic thinking, which lacks human focus. Energy culture has been identified as a research domain that successfully overcomes the traditional techno-economic focus of technology diffusion. However, available energy culture studies on adopting energy-efficient technology innovations in buildings are limited to exploring specific energy cultures rather than investigating holistic energy culture maturity, which guides incremental diffusion of energy-efficient technology innovations. Conversely, culture maturity has been studied in other cultural research domains such as safety cultures. Therefore, this study aims to develop an energy culture maturity conceptual framework that provides a holistic view of energy culture maturity for adopting energy-efficient technology innovations in buildings. The research method this study implemented was a scoping literature review method, using Web of Science, Scopus, and Engineering Village research databases. The findings of the study include the development of factor categorisation with 14 main factors and 11 subfactors and the development of three energy culture maturity stages, as well as the development of the energy culture maturity conceptual framework as the principal outcome. The proposed conceptual framework significantly contributes to energy culture research as the pioneering framework on energy culture maturity. The framework should be further tested and applied to find its utility.